Kahoot! as a Pedagogical Tool in IELTS Writing Instruction: A Qualitative Analysis of Gamified Learning Strategies - Rowiyah, Siti (Universitas Hamzanwadi, 2024)
Writing is one of the four primary skills assessed in the International English Language Testing System (IELTS). Its inherent complexity often leads to student anxiety and difficulties. Recognizing the need for innovative teaching and assessment methods incorporating technology, this study investigates the interactive game Kahoot! in an IELTS writing course in Pare, Kediri. Despite evidence supporting its effectiveness, Kahoot!'s integration into academic writing still needs to be improved. This research aims to evaluate how Kahoot! Enhances students' fluency in academic writing within an IELTS context and identifies factors influencing this relationship. Conducted through a qualitative, descriptive case study approach, the study involves English teachers and their students who use Kahoot! in academic IELTS writing classes. Findings indicate that Kahoot! Primarily aids in understanding writing tasks by simplifying data complexity and integrating it into engaging game features, thus enhancing learning engagement and task response. Key factors contributing to improved writing responses include the simplicity of visual presentation, the competitive nature of the game, and the resulting enjoyment. This suggests that Kahoot! can effectively create a dynamic and enjoyable learning environment, potentially improving academic writing performance in IELTS courses.